Hubungan pola asuh orang tua dan lingkungan teman sebaya dengan masalah mental emosional remaja di SMP N 2 Sokaraja - Nur Kholifah; Sodikin Sodikin (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: To find out the correlation between parenting style and peer environment with adolescent emotional mental problems in SMP N 2 Sokaraja. Method: This was a quantitative descriptive correlational research with a cross-sectional approach. There were 107 respondents from 7th and 8th grade taken as the research sample using a proportional stratified random sampling technique. The data obtained were analyzed using Chi-Square test. Results: The results showed that 43.9% male respondents and 56,1% female respondents. The average age of the respondents was 13 years. There were three parenting styles applied by the respondents parents namely permissive parenting (25 respondents / 23.4%), authoritarian parenting (44 respondents / 41.1%) and democratic parenting (38 respondents / 35.5%). The peer environment of 41 respondents (38.3%) was in a good category, while that of the rest (66 respondents / 61.7%) was in a poor category. There were 69 respondents (64.5%) who experienced emotional mental problems and the rest (35.5%) did not. Based on the results of the bivariate analysis, the significance level of parenting was 0,000 (0.000 < 0,05) and that of the peer environment was 0.002 (0.002 < 0,05). Conclusion: There is a correlation between parenting style and peer environment with adolescent emotional mental problems in SMP N 2 Sokaraja.Keywords: adolescents, emotional mental, parenting